PEMBENTUKAN SIKAP SOSIAL PESERTA DIDIK MELALUI PEMBELAJARAN IPS KELAS VIII B di SMP NEGERI 8 PONTIANAK - Ardita, Lilis; Mashudi, Mashudi; Aminuyati, Aminuyati; Wiyono, Hadi; Atmaja, Thomy Sastra (Universitas Tanjungpura, 2023)
This study aims to determine the formation of students' social attitudes through social studies learning, especially class VIII B at SMP Negeri 8 Pontianak. The form of research used in this research is qualitative with descriptive method. The subjects of this study were 1 social studies teacher for class VIII and 8 students for class VIII B at SMP Negeri 8 Pontianak. Data collection techniques used are observation, interviews, and documentation and data analysis techniques obtained through three stages, namely, data reduction, data presentation and conclusion. The results of this study indicate that: the formation of social attitudes through social studies learning in class VIII B students at SMP Negeri 8 Pontianak has been carried out well, teachers at SMP Negeri 8 Pontianak are trying to guide, direct and advise students who make mistakes. Overall, the social attitudes of students at SMP Negeri 8 Pontianak are seen as good, but there are some students whose social attitudes are still lacking. For this reason, teachers, especially social studies teachers, are still trying to educate their students to be better. The social attitudes that are formed are honest, disciplined, responsible, polite, caring and confident, where the social attitudes that are formed can make students have better attitudes in the family, school and community environment.